Web-Based Incoming And Outgoing Mail Information System As An Effort To Optimize Administration At The Secretariat Of The Regional House Of Representatives (DPRD) Of Minahasa Regency Using The Prototype Method - Brandon Natanael Gerungan; Gladly Caren Rorimpandey (Jurnal Media Computer Science, 2026)
Correspondence administration is one of the key aspects in supporting the smooth functioning of bureaucracy in government institutions, including at the Secretariat of the Regional House of Representatives (DPRD) of Minahasa Regency. The current manual management of incoming and outgoing letters often leads to various issues, such as delays in recording, data entry errors, and difficulties in retrieving archived correspondence. Therefore, this study aims to design and develop a web-based information system for managing incoming and outgoing letters to optimize administrative processes within the DPRD Secretariat. The system development follows the prototype method, which allows users to provide direct feedback on the initial system model for iterative improvements. The result of this research is a web-based application that facilitates effective and efficient recording, archiving, searching, and reporting of correspondence. With the implementation of this system, it is expected that the letter administration process at the Secretariat of the DPRD Minahasa Regency will become faster, more accurate, and well-documented.